2018
DOI: 10.1038/s41598-018-21373-2
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and clinical characteristics of ciguatera fish poisoning in Guadeloupe (French West Indies) between 2013 and 2016: a retrospective cases-series

Abstract: This retrospective case study analysed the incidence and symptoms of ciguatera fish poisoning (ciguatera) in Guadeloupe (French West Indies) between 2013 and 2016. Cases attending the emergency departments of the two public hospitals and the reports received by the regional health authority in charge of monitoring (ARS) were compiled. Two hundred and thirty-four cases of poisoning were observed, with a mean annual incidence of 1.47/10,000 (95% CI): 1.29–1.66), i.e 5 times higher than the previously reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…One of the more frequent and characteristic neurological symptoms is cold allodynia, a misperception in which contact with cold surfaces triggers a burning or painful sensation. Other neurological signs associated with ciguatera include hand, feet or perioral paresthesias, dizziness, pruritus, taste alterations, arthralgia, myalgia, hypothermia, and headache [ 62 , 80 , 84 ]. Dental pain or loose teeth sensation have also been reported.…”
Section: Ciguatoxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the more frequent and characteristic neurological symptoms is cold allodynia, a misperception in which contact with cold surfaces triggers a burning or painful sensation. Other neurological signs associated with ciguatera include hand, feet or perioral paresthesias, dizziness, pruritus, taste alterations, arthralgia, myalgia, hypothermia, and headache [ 62 , 80 , 84 ]. Dental pain or loose teeth sensation have also been reported.…”
Section: Ciguatoxinsmentioning
confidence: 99%
“…Alterations of the cardiovascular function consistent of hypotension and bradycardia may also be present concurrently with gastrointestinal and neurologic signs during the acute phase. Although cardiovascular symptoms are considered indicative of severe intoxication [ 87 , 88 ], recent retrospective studies suggest that their incidence is probably higher than initially reported [ 84 ].…”
Section: Ciguatoxinsmentioning
confidence: 99%
“…180 nautical miles to the southeast of the study location) has implemented measures to protect the population against the threat of CFP posed by L. apodus, and 15 other species, through a Prefectural order (N • 2002-1249) restricting their harvest and sale. O. chrysurus have no sales restrictions regarding CFP [17,18]. According to hospital emergency department cases and regional monitoring networks in Guadeloupe, there were 16 cases of CFP between 2013-2016 where either L. jocu or L. apodus were implicated in the poisoning (species confirmation was unavailable due to a lack of genetic identification) [18].…”
Section: Introductionmentioning
confidence: 99%
“…O. chrysurus have no sales restrictions regarding CFP [17,18]. According to hospital emergency department cases and regional monitoring networks in Guadeloupe, there were 16 cases of CFP between 2013-2016 where either L. jocu or L. apodus were implicated in the poisoning (species confirmation was unavailable due to a lack of genetic identification) [18]. O. chrysurus was implicated in only one case of CFP out of 234, however, genetic confirmation was not performed and this species was labeled as 'not considered to be responsible for CFP at the time of reporting' [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation